1989
DOI: 10.1073/pnas.86.22.8650
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of O6-substituted guanine-induced mutagenesis of ras oncogenes.

Abstract: We have designed an Ha-ras/thymidine kinase (TK) cassette that permits the incorporation of chemically synthesized adducts within specific domains of the rat Ha-ras protooncogene. This cassette has been used to evaluate the mutagenicity of O6-substituted guanine residues, including 06-methylguanine and 06-benzylguanine, incorporated within the 12th codon of this locus. Mutations were monitored by the ability of these modified Ha-ras DNAs to transform Rat4 TKcells. Our results indicate that both types of 06-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 27 publications
(34 reference statements)
2
60
1
Order By: Relevance
“…Thus, O 6 -methylguanine is read as an adenine and mispairs with thymine (Horsfall et al, 1990). Supporting these data, the most common mutations caused by alkylating agents are G : C to A : T transitions (Horsfall et al, 1990), exemplified in the frequent generation of G to A transitions in the oncogene K-ras when the carcinogen N-methylnitrosourea (that forms O 6 -methylguanine adducts) is used in experimentally induced tumor systems (Sukumar et al, 1983;Mitra et al, 1989). Avoidance of the mutagenic effect is directly related to the presence of a functional MGMT protein (Pegg et al, 1995).…”
Section: Silencing Of Mgmt Causes a New Mutator Pathway In Human Cancermentioning
confidence: 63%
“…Thus, O 6 -methylguanine is read as an adenine and mispairs with thymine (Horsfall et al, 1990). Supporting these data, the most common mutations caused by alkylating agents are G : C to A : T transitions (Horsfall et al, 1990), exemplified in the frequent generation of G to A transitions in the oncogene K-ras when the carcinogen N-methylnitrosourea (that forms O 6 -methylguanine adducts) is used in experimentally induced tumor systems (Sukumar et al, 1983;Mitra et al, 1989). Avoidance of the mutagenic effect is directly related to the presence of a functional MGMT protein (Pegg et al, 1995).…”
Section: Silencing Of Mgmt Causes a New Mutator Pathway In Human Cancermentioning
confidence: 63%
“…All mutations were found at the 2nd position of the 12th codon (rather than on the 1st position, see Figure 4). This latter Ā®nding also holds for ras gene mutations at the same codon in for instance MNNG-or MNU-induced mouse skin tumors (Mitra et al, 1989;Brown et al, 1990Brown et al, , 1995. Further analysis of the same set of 28 tumors revealed that additionally one papilloma and one SCC carried a K12-ras gene mutation (also a G?A transition at the 2nd position of the codon, results not shown).…”
Section: Xpamentioning
confidence: 88%
“…Alkylating agents, for example, when applied on the skin of wild type mice, induce papillomas by targeting the 2nd G residue in codon 12 of the H-ras gene, resulting in a G?A transition like we found in U.V.B.-induced papillomas of XPA-deĀ®cient mice ( Figure 5 and references. Mitra et al, 1989;Brown et al, 1990Brown et al, , 1995. Furthermore, the main genetic target of the classical skin carcinogen DMBA in papilloma development, is an A-residue in codon 61 of the mouse Hras gene (Brown et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…To assess the ability of 8 hydroxydeoxyguanosine to induce K-ras oncogene activation, we utilized the pGM 22 mammalian expression vector (Mitra et al, 1989), which contains codons 1 Ā± 8 and codons 14 Ā± 189 of a nontransforming (codon 59=Ala) v-H-ras clone, separated by a 1.3 kb spacer fragment. pGM 22 was digested with BspMI to remove the spacer fragment, and a full-length ras gene, containing 8 hydroxydeoxyguanosine at codon 12, was reconstituted by ligating a synthetic double-stranded oligonucleotide (encoding codons 9 Ā± 13 of K-ras and containing 8 hydroxydeoxyguanosine substituted for deoxyguanosine at either the Ā®rst or second position of codon 12) into the BspMl site of PGM 22.…”
Section: Incorporation Of 8 Hydroxydeoxyguanosine Into Codon 12 Of Ramentioning
confidence: 99%